Raising the level of water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Towards sustainable water resources management European Commission, 1998, 350 pp. ISBN 92 828 4456 0 Free of charge DG Development, Rue de la Loi 200, B1049 Brussels Fax: + 32 2 299 25 25 Email: info@cec.eu.int